Guanidine-catalyzed asymmetric Strecker reaction: modes of activation and origin of stereoselectivity - Xue, Hansong (2017)
Density functional theory calculations were employed to study the catalytic mechanism, modes of activation, and origin of enantioselectivity of guanidine-catalyzed asymmetric Strecker reaction of N-benzhydryl imine with hydrogen cyanide. Two types of bifunctional activation mode were identified, namely conventional bifunctional Brønsted acid activation and unconventional bifunctional Brønsted–Lewis acid activation. The lowest-energy transition states correspond to the conventional bifunctional mode of activation. The calculated enantiomeric excess, based on eight lowest-energy C–C bond forming transition states, is in good accord with observed enantioselectivity. NCI (noncovalent interaction) analysis of the key transition states reveals extensive noncovalent interactions, including aromatic interactions and hydrogen bonds, between the guanidinium catalyst and substrates. Multiple aryl–aryl interactions between the phenyl groups of guanidine catalyst and the phenyl rings of N-benzhydryl imine are the key stabilizations in the most stable (R)-inducing transition state. Differential attractive aryl–aryl stabilization is the major factor for stereoinduction.